2022
DOI: 10.3389/fpls.2021.764843
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Host and Parasitic Plant Interaction by Tissue-Specific Gene Analyses on Tomato and Cuscuta campestris Interface at Three Haustorial Developmental Stages

Abstract: Parasitic weeds cause billions of dollars in agricultural losses each year worldwide. Cuscuta campestris (C. campestris), one of the most widespread and destructive parasitic plants in the United States, severely reduces yield in tomato plants. Reducing the spread of parasitic weeds requires understanding the interaction between parasites and hosts. Several studies have identified factors needed for parasitic plant germination and haustorium induction, and genes involved in host defense responses. However, kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 79 publications
(113 reference statements)
0
13
0
Order By: Relevance
“…In root parasites of Orobanchaceae ( Triphysaria versicolor , Striga hermonthica , and Phelipanche aegyptiaca ), molecular evidence indicates that they evolutionarily recruited many genes for haustorial development and host penetration from genes that were involved in other processes in related non-parasitic plants, primarily root ( Sun et al, 2018 ) or flower development, but with some genes co-opted from other tissues ( Yang et al, 2015 ; Yoshida et al, 2016 ). These putative parasitism genes are also upregulated in the haustoria of Cuscuta campestris ( Ranjan et al, 2014 ), and auxin-mediated regulation of haustorium initiation shared by both root and stem parasitic plants ( Yoshida et al, 2016 ; Jhu et al, 2021 , 2022 ), would support the hypothesis that stem parasites also co-opted the root parasite program into haustorium development. Based on this, some authors proposed that haustoria might be interpreted as morphological misfits ( Rutishauser and Isler, 2001 ; Teixeira-Costa, 2021a ).…”
Section: Discussionmentioning
confidence: 86%
“…In root parasites of Orobanchaceae ( Triphysaria versicolor , Striga hermonthica , and Phelipanche aegyptiaca ), molecular evidence indicates that they evolutionarily recruited many genes for haustorial development and host penetration from genes that were involved in other processes in related non-parasitic plants, primarily root ( Sun et al, 2018 ) or flower development, but with some genes co-opted from other tissues ( Yang et al, 2015 ; Yoshida et al, 2016 ). These putative parasitism genes are also upregulated in the haustoria of Cuscuta campestris ( Ranjan et al, 2014 ), and auxin-mediated regulation of haustorium initiation shared by both root and stem parasitic plants ( Yoshida et al, 2016 ; Jhu et al, 2021 , 2022 ), would support the hypothesis that stem parasites also co-opted the root parasite program into haustorium development. Based on this, some authors proposed that haustoria might be interpreted as morphological misfits ( Rutishauser and Isler, 2001 ; Teixeira-Costa, 2021a ).…”
Section: Discussionmentioning
confidence: 86%
“…Haustorial invasion is also facilitated by mechanical action and by biochemical degradation and modification of host cell walls ( Nagar et al, 1984 ; Olsen et al, 2016 ; Hozumi et al, 2017 ). Many genes encoding cell wall degrading and modifying enzymes were upregulated haustorium ( Ranjan et al, 2014 ; Ikeue et al, 2015 ; Jhu et al, 2022 ). Furthermore, the dynamics of cell wall components were observed by the penetration of haustorium into the host tissue ( Johnsen et al, 2015 ; Hozumi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since stable gene knockout approaches for Cuscuta plants is currently not available, it has not been possible to access in vivo function of CcERF52A and CcERF52B. However, it has recently been reported that the host-derived siRNAs could successfully down-regulate target gene transcription in C. campestris, via a host-induced gene silencing (HIGS) system ( Jhu et al, 2022 ). One of the challenges is the use of HIGS system for knockdown of CcERF52A and CcERF52B in C. campestri s. Further investigation of the relationship between CcERF52s and the cell wall enzyme genes will be needed to support our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haustorial invasion is also facilitated by mechanical action and by biochemical degradation and modification of host cell walls (Nagar et al, 1984;Olsen et al, 2016;Hozumi et al, 2017). Many genes encoding cell wall degrading and modifying enzymes were upregulated haustorium (Ranjan et al, 2014;Ikeue et al, 2015;Jhu et al, 2022). Furthermore, the dynamics of cell wall components were observed by the penetration of haustorium into the host tissue (Johnsen et al, 2015;Hozumi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%